A la ciudad en la bahía… (2017)
Today I am in a world of waterWhere everything was drawn around himEveryone looks at the bay,But you, doveIt seems that you look at something differentA small inveral world of water and leaf litterAn urban oasis,ephemeral, voluble, mobile and changing ...Where everyone can beWithout fear of freedomIt's the big cityA place where it is permissible to floatAre you the sum of parallel universes?Of convergent freedoms that express themselves infinitely?For many,your freedom is just that,a reflection of an unthinkable realityFor you, pigeon, the ground where you can beAnd look beyondIn you, even iffor a moment,water reflection,mirror of freedom,let me walk,let me dream,let me live,let me fly…Let me meet you,once again…